Minimizing Sensor Failures in Wireless Rechargeable Sensor Networks With Obstacles Through Fresnel Diffraction Model - Kun Wang; Zhejun Shen (IEEE Journal of the Electron Devices Society)
In this paper, we mainly focus on the charging scheduling problem in Wireless Rechargeable Sensor Networks (WRSNs) with obstacles. We first describe the influences of obstacles on the charging signals through the Fresnel Diffraction Model (FDM). Then we design the spatial and time discretization methods, whose approximate ratios are precisely determined to reduce the computational complexity of the charging optimization problem. On this basis, we design methods to select the charging spots and determine the corresponding charging time to minimize the number of sensor failures. Besides, we also design an effective obstacle avoidance navigation algorithm, which can enable the Mobile Chargers (MCs) to avoid obstacles effectively reducing the moving distances. Simulations are conducted to verify the advantages of our scheme, revealing that our scheme outperforms in terms of the failure sensor number, charging utility, and so on.